Claiming publicness for work - Lopes, H. (2012)
Abstract: Mainstream economists and social philosophers like Arendt and Habermas conceive work as an instrumental activity. This instrumental conception of work results from the way in which work is regarded: as a relation between men and nature rather than a relation between men. Work is then relegated to the private, non-political domain. Conversely, we argue that work entails a co-operative and intersubjective character, which endows work, as experienced by workers, with an inescapable political and public dimension. These analytical claims lead us to question the strict distinction between the public and the private in contemporary democratic societies and adopt a normative perspective. Major normative implications are that work-related issues should be transformed from private practices to public matters and that participatory workplaces should be promoted by public regulation.